The impact of students’ self-confidence in their learning process - Engelina Salainti (Sean Institute, 2024)
One of the crucial factors in learning English as a second language is having good self-confidence. Some students found difficulties and struggles with a lack of confidence and self-doubt, while other students found that self-confidence is the key to their success. This study aims to explore the measurement of students’ self-confidence and find the impact on their learning process at Universitas Klabat. This study is a description of the quantitative questionnaire and the data collected through a sampling of 40 students male and female from an Intermediate II English class from 3 faculties: Economics and Business, Philosophy and Computer Science. The findings revealed that there are some students had low self-confidence and most students were highly self-confident. The result showed that the students’ self-confidence affected their learning in some areas, participation, seeking goals, decreasing anxiety, developing interest in lessons, being comfortable with their teachers and classmates, and sharing their opinions that related to the lesson in their class.